Gastroprotective Effects of Aqueous Extracts of Broccoli Stems on Acute Injury in Rats: A Comprehensive Evaluation of Gastric Function and Inflammatory Responses - Jihye Choi; Yuseong Jang; Hyeon-Gi Paik; Melissa Hyun-Joo Ha; Jungkee Kwon (Medicina)
Background and Objectives: Acute gastric injury is a prevalent gastrointestinal disorder characterized by inflammation and damage to the stomach lining. In this study, we investigated the therapeutic potential effects of broccoli stem extract (BSE) against acute gastritis in a rat model. Materials and Methods: The antioxidant properties of BSE were evaluated through DPPH and ABTS radical scavenging activity assays and total polyphenol content analysis. Acute gastric injury was induced using 150 mM HCl/60% EtOH, and male SD rats (6-weeks old, n = 6/group) were administered BSE by oral gavage at concentrations of 50, 125, and 250 mg/kg. Results: The BSE 250 mg/kg group exhibited significant relief of clinical signs compared to the negative control group. In addition, the BSE 250 mg/kg group showed significant improvements in gastric tissue, including macroscopic reductions in ulcer size and improved overall gastric morphology as assessed through gross examination, as well as microscopic improvements such as reduced inflammation and the restoration of mucosal integrity observed in histopathological analysis. BSE modulated NF-κB signaling, decreased inflammatory cytokines (TNF-α, IL-1β, and IL-6), and increased PGE2 levels. Pyloric ligation experiments demonstrated reduced pepsin and gastric acid secretion. Improvements in gastric emptying and gastrointestinal motility were also observed in the BSE-treated group. Conclusions: These findings highlight the potential of BSE as an effective therapeutic agent for acute gastritis in rats, offering significant improvements in gastric damage, inflammation, and motility.